Dips and floors in workplace training: Using personnel records to estimate gender differences - Bernd Fitzenberger; Grit Muehler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
Using personnel records from a single large German firm in the financial industry, this paper provides detailed evidence on the effect of age and the supervisor's gender on gender differences in workplace training, holding constant various workplace characteristics. We implement an age-specific decomposition of the incidence and the duration of training into three terms: an age-specific coefficients effect, an age-specific characteristics effect, and an age composition effect. Our results show that the gender training gap changes with age. Females obtain less training during the early career, and their training occurs at higher age. The timing of the gender training gap seems to be driven by diverging career paths associated with employment interruptions. However, we find no evidence for catching-up effects after parental leave. A decomposition of the training gap including supervisor fixed effects reveals that supervisors do not treat male and female employees differently. Supervisors assign more training to all employees if they themselves participate more in training.
urn:nbn:de:bsz:180-madoc-31680
Keywords: M53; M12; J14; 330; training participation; age; gender; company data